Development of programming language Espace and its application to parallel and distributed evolutionary computation - Iwakawa, Takehiko; Ono, Satoshi; Nakayama, Shigeru (Artificial life and robotics, 2009)
This article proposes a programming language called “Espace” for parallel and distributed computation. In general, it is difficult to code a distributed, parallel program due to multi-threading, message passing, managing clients, and so on. Espace involves a few simple syntax rules added to Java. Developers do not need to know how to write a parallel, distributed program source code in detail. This work applies Espace to parallelize an evolutionary computation program, and shows that the Espace compiler allows the conversion of an evolutionary computation program written in Java into a distributed, parallel system by adding a few words to the program.